2022
DOI: 10.1021/acs.jpca.2c00201
|View full text |Cite
|
Sign up to set email alerts
|

Basis Set Dependence of Optical Rotation Calculations with Different Choices of Gauge

Abstract: In this work, the basis set dependence of optical rotation (OR) calculations is examined for various choices of gauge/level of theory. The OR is calculated for a set of 50 molecules using B3LYP and CAM-B3LYP and 17 molecules using coupled cluster with single and double excitations (CCSD). The calculations employ the correlation-consistent basis sets, aug-cc-pVζZ with ζ = D, T, Q. An inverse-power extrapolation formula is then utilized to obtain OR values at the complete basis set (CBS) limit. We investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 74 publications
(168 reference statements)
1
18
0
Order By: Relevance
“…This indicates that this basis set is close to completeness for this system and the calculations approach gauge invariance. 64 The PBC-MVG value in Table III is in very good agreement with the value reported in Ref. 37: 36.1 deg L dm −1 mol −1 (the small discrepancy is due to the extreme sensitivity of this property to unavoidable differences in numerical thresholds between different implementations).…”
Section: B Comparison With Cluster Modelssupporting
confidence: 86%
See 1 more Smart Citation
“…This indicates that this basis set is close to completeness for this system and the calculations approach gauge invariance. 64 The PBC-MVG value in Table III is in very good agreement with the value reported in Ref. 37: 36.1 deg L dm −1 mol −1 (the small discrepancy is due to the extreme sensitivity of this property to unavoidable differences in numerical thresholds between different implementations).…”
Section: B Comparison With Cluster Modelssupporting
confidence: 86%
“…The error for the OR is larger (about 50% if the latest experimental value of −12.3 ± 1.0 deg/mm is considered), but it is consistent with the error for the isotropic OR of molecules at this level of theory. 59,64 The choice of gauge is less important than that of the level of theory as the MVG and LG(OI) results are very close to each other. This is also confirmed by the polar plots representation of the OR tensors in Figure 4-5.…”
Section: Mvgmentioning
confidence: 82%
“…Grimme et al suggested a simplified TDDFT (sTDDFT), which is so cheap to allow many calculations on several snapshots taken from a preliminary molecular dynamics (MD) 8 calculation, or an automated procedure to treat flexible molecules 9 . From a different perspective, Caricato et al have studied the problem of the gauge choice in optical rotation 10–14 . Mennucci et al worked on excitonic models 15 while Cappelli on the chiroptical properties in aqueous solution 16 .…”
Section: Introductionmentioning
confidence: 99%
“…LG(OI) Exp. 59,64 The choice of gauge is less important than that of the level of theory as the MVG and LG(OI) results are very close to each other. This is also confirmed by the polar plots representation of the OR tensors in Figure 4-5.…”
Section: Mvgmentioning
confidence: 82%